2016
DOI: 10.1111/add.13387
|View full text |Cite
|
Sign up to set email alerts
|

A mixed-method systematic review and meta-analysis of mental health professionals' attitudes toward smoking and smoking cessation among people with mental illnesses

Abstract: Background and aimsPeople with mental illnesses and substance abuse disorders are important targets for smoking cessation interventions. Mental health professionals (MHPs) are ideally placed to deliver interventions, but their attitudes may prevent this. This systematic review therefore aimed to identify and estimate quantitatively MHPs attitudes towards smoking and main barriers for providing smoking cessation support and to explore these attitudes in‐depth through qualitative synthesis.MethodsThe online data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
152
1
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(166 citation statements)
references
References 65 publications
9
152
1
4
Order By: Relevance
“…The belief that smoking cessation will interfere with efforts to attain or maintain sobriety is common among those with alcohol use disorder (Gulliver, Kamholz, & Helstrom, 2006; Martin, Rohsenow, MacKinnon, Abrams, & Monti, 2006). Moreover, beliefs that smoking cessation will interfere with SUD treatment may be reinforced by similar beliefs among some clinicians (Bobo, Slade, & Hoffman, 1995; Pagano, Tajima, & Guydish, 2016; Richter, 2006; Sheals, Tombor, McNeill, & Shahab, 2016), as well as limited availability of smoking cessation services in SUD treatment settings (Currie, Nesbitt, Wood, & Lawson, 2003; Knudsen, in press; Knudsen, Muilenburg, & Eby, 2013; Knudsen, Studts, Boyd, & Roman, 2010; Nahvi, Blackstock, Sohler, Thompson, & Cunningham, 2014). Thus, individuals presenting to SUD treatment have particularly poor smoking cessation rates and are vulnerable to a broader array of potential barriers to smoking cessation relative to those without SUDs, highlighting the importance of understanding barriers to smoking cessation in this population.…”
Section: Introductionmentioning
confidence: 99%
“…The belief that smoking cessation will interfere with efforts to attain or maintain sobriety is common among those with alcohol use disorder (Gulliver, Kamholz, & Helstrom, 2006; Martin, Rohsenow, MacKinnon, Abrams, & Monti, 2006). Moreover, beliefs that smoking cessation will interfere with SUD treatment may be reinforced by similar beliefs among some clinicians (Bobo, Slade, & Hoffman, 1995; Pagano, Tajima, & Guydish, 2016; Richter, 2006; Sheals, Tombor, McNeill, & Shahab, 2016), as well as limited availability of smoking cessation services in SUD treatment settings (Currie, Nesbitt, Wood, & Lawson, 2003; Knudsen, in press; Knudsen, Muilenburg, & Eby, 2013; Knudsen, Studts, Boyd, & Roman, 2010; Nahvi, Blackstock, Sohler, Thompson, & Cunningham, 2014). Thus, individuals presenting to SUD treatment have particularly poor smoking cessation rates and are vulnerable to a broader array of potential barriers to smoking cessation relative to those without SUDs, highlighting the importance of understanding barriers to smoking cessation in this population.…”
Section: Introductionmentioning
confidence: 99%
“…The themes extracted in this study agree with those seen in other healthcare scenarios. Sheals et al (2016) performed a systematic review of smoking cessation attitudes in mental health professionals where the most frequently perceived barriers were lack of knowledge or training followed by lack of time and low confidence 43 .…”
Section: Discussionmentioning
confidence: 99%
“…The authors found that approximately 40% of participants from all included studies held negative attitudes to cessation where practitioners believed patients were not interested in quitting smoking and that smoking cessation interventions were not effective 43 . Similarly, 38% of GPs view discussing smoking with patients as ineffective 44 .…”
Section: Discussionmentioning
confidence: 99%
“…Smoking cessation guidelines for people with SMI also need to address practitioner barriers such as time and financial constraints and competing priorities in delivering smoking cessation (Sheals et al, 2016). Cost-effectiveness and affordability are particularly relevant for both practitioners and their patients, given that many smokers with SMI have limited incomes (Francke et al, 2008).…”
Section: Agree Evaluationmentioning
confidence: 99%